Development of Animated Comic Media Containing Local Wisdom "Learning the Culture of Dam Bagong Trenggalek" to Improve Cultural Literacy Students Grade IV Elementary School - Duwi Ika Pitri Hardianti; Indah Yunitasari; Angga Setiawan (JOSAR (Journal of Students Academic Research), 2025)
Cultural literacy is an important part of learning to support the Independent Curriculum, especially on the theme of exploring local wisdom. However, the younger generation's attention to local culture is decreasing due to modern developments. This study aims to develop an animated comic media containing local wisdom "Learning the Culture of Dam Bagong Trenggalek" to improve the cultural literacy students grade IV elementary school. The method used is Research and Development (R&D) with the ADDIE development model. The research sample consisted of 90 students from four elementary schools in Trenggalek District, namely SDN 2 Ngantru, SDN 2 Surodakan, SDN 1 Sumbergedong, SDN 3 Tamanan with a purposive sampling technique. Data collection techniques included observation, interviews, questionnaires, tests, and documentation. The validation results showed a score of 93% for media experts, 92.5% for material experts, and 92.5% for language experts, which is classified as very valid. The practitioner's assessment obtained a score of 97.5% and is classified as very practical. The effectiveness test showed an increase in pretest and posttest results of 32.5% on a field scale. The hypothesis test showed a significance value of 0.000 < 0.05. The N-Gain value of 86.12 is included in the high category. Student responses to the media reached 99.34% and were classified as very interesting. The results of the study concluded that the animated comic media containing local wisdom "Learning the Culture of Dam Bagong Trenggalek" is very valid, practical, interesting, and effective in improving the cultural literacy students grade IV elementary school.